2016
DOI: 10.1094/phyto-02-16-0054-fi
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study in Wheat Identifies Resistance to the Cereal Cyst Nematode Heterodera filipjevi

Abstract: The cyst nematode Heterodera filipjevi is a plant parasite causing substantial yield loss in wheat. Resistant cultivars are the preferred method of controlling cyst nematodes. Association mapping is a powerful approach to detect associations between phenotypic variation and genetic polymorphisms; in this way favorable traits such as resistance to pathogens can be located. Therefore, a genome-wide association study of 161 winter wheat accessions was performed with a 90K iSelect single nucleotide polymorphism (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 73 publications
2
30
1
Order By: Relevance
“…The process of effective recombination events in A and B genomes might have resulted from the historical development of hexaploid wheat and its domestication process 2,33 . Consistent with our previous findings, A and B genomes have higher polymorphism than D genome 19,24 . Würschum et al 34 reported similar finding of few SNPs to be located on the D genome of 172 European winter wheat cultivars 34 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The process of effective recombination events in A and B genomes might have resulted from the historical development of hexaploid wheat and its domestication process 2,33 . Consistent with our previous findings, A and B genomes have higher polymorphism than D genome 19,24 . Würschum et al 34 reported similar finding of few SNPs to be located on the D genome of 172 European winter wheat cultivars 34 .…”
Section: Discussionsupporting
confidence: 93%
“…The flanking sequences of the significant markers were blasted against gene models of Brachypodium distachyon, Oryza sativa, and Sorghum bicolor, IWGSC, the Institute for Genomic Research (TIGR) Wheat genome annotation, and National Center for Biotechnology Information (NCBI). The genes/proteins were selected based on significant hit and lowest expect e-value 24 . The wheat transcriptome assemblies from MAS Wheat dataset 71 were downloaded and the full open reading frame (ORF) at significant marker locations were identified.…”
Section: Principle Component and Relatedness Analysis Principal Compmentioning
confidence: 99%
See 1 more Smart Citation
“…The study revealed three DArT markers for four novel H. avenae resistance QTL. In a separate study, resistance to H. filipjevi was revealed in winter wheat accessions from the International Wheat Improvement Program using the 90K SNP platform [57]. Resistance was based on counts of cysts and females in root and soil samples, and was associated with 11 QTL.…”
Section: New Sources Of Genetic Resistance To Nematodes Of Small-graimentioning
confidence: 99%
“…The rye cyst nematode ( H. filipjevi ), like other CCNs, is an obligate biotrophic sedentary endoparasite, mainly infesting barley and wheat (Dababat and Fourie, ). As a result of H. filipjevi feeding on roots of infected plants the grain yield losses may reach up to 50% (Pariyar et al , ). The infective second‐stage juvenile (J2) of CCN damages the host root cell wall using its stylet and hydrolytic enzymes synthesized in oesophageal glands and secreted through the stylet orifice.…”
Section: Introductionmentioning
confidence: 99%